Health and nutrition emergency response among internally displaced persons at Ranch collective site, Chagni, Ethiopia: The role of emergency operation center, lessons from the field, and way forwards - Alemu, Tefera; Bezabih, Belay; Amsalu, Abraham; Hassen, Eyaya; Haile, Mahteme; Abite, Melkamu (Frontiers in Public Health, 2022)
Abstract Background: In October 2020 and onwards, a total of 79,041 ethnically Amhara/Agew people have been displaced from Metekel zone of Benishangul-Gumuz region and resided in Ranch collective site, Chagni town. The aim of the response was to ensure that health and nutrition emergency responses are delivered according to disaster response standards. Methods: On January 11/2021, the Amhara Public Health Institute (APHI) established an onsite Public Health Emergency Operation Center (PHEOC) in Chagni/Ranch collective site. Health workers and vehicles were allocated. A temporary clinic having nine outlets were built. Drugs and medical supplies were mobilized from different sources. The overall response period lasted about eight months from December 2020 up to June 2021. Results: A total of 33,410 IDPs had received free essential health services. Mental health services have been given for 1,803 cases. Specialized medical services like trachomatous trichiasis (30), cataract surgery (8) and sputum sample for tuberculosis (120) have been done. Moreover, 454 women received antenatal care service and 137 women gave birth at health facilities. About 837 children have got measles supplementary dose and 1280 adults took COVID-19 vaccination. A total of 1448 under-five children, 454 pregnant and 402 lactating women have been screened on monthly basis. Of which, severe and moderate malnutrition rate was 46(3.2%) and 75 (5.2 %) respectively. A total of 194 trench latrine seats, 74 shower rooms and 50 hand washing facilities has been constructed. Generally, there were no human feces present nor solid wastes accumulated around the shelters or settlement. Conclusion: Health and nutrition services at Ranch collective site were delivered according to the standards in sphere humanitarian guidelines. Responding through a PHEOC, having a pre-existing buildings and infrastructures for collective center and high-level preparedness are the pertinent lessons we took for effective response. Keywords: Health, Nutrition, PHEOC, Ranch collective site